Mechanism of Enhancing Pyrazines in Daqu via Inoculating Bacillus licheniformis with Strains Specificity - Qiuxiang Tang; Xiaoru Chen; Jun Huang; Suyi Zhang; Hui Qin; Yi Dong; Chao Wang; Xiaojun Wang; Chongde Wu; Yao Jin; Rongqing Zhou (Foods, 2023)
Despite the importance of pyrazines in Baijiu flavor, inoculating functional strains to increase the contents of pyrazine in Daqu and how those interact with endogenic communities is not well characterized. The effects of inoculating Bacillus licheniformis with similar metabolic capacity on pyrazine and community structure were assessed in the Daqu complex system and compared with traditional Daqu. The fortification strategy increased the volatile metabolite content of Daqu by 52.40% and the pyrazine content by 655.99%. Meanwhile, results revealed that the pyrazine content in Daqu inoculated isolate J-49 was 2.35–7.41 times higher than isolate J-41. Both isolates have the almost same capability of 2,3-butanediol, a key precursor of pyrazine, in pure cultured systems. Since the membrane fatty acids of isolate J-49 contain unsaturated fatty acids, it enhances the response-ability to withstand complex environmental pressure, resulting in higher pyrazine content. PICRUSt2 suggested that the increase in pyrazine was related to the enzyme expression of nitrogen metabolism significantly increasing, which led to the enrichment of NH4+ and 2,3-butanediol (which increased by 615.89%). These results based on multi-dimensional approaches revealed the effect of functional bacteria enhancement on the attribution of Daqu, laid a methodological foundation regulating the microbial community structure and enhanced the target products by functional strains.